The Effect of Mismanagement and Embezzlement of Funds in the Public Sector - Izunna Ogudu Chukwu (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
Mismanagement and embezzlement of public funds are pervasive issues in the public sector, particularly in developing nations where governance structures are weak. These malpractices divert resources meant for infrastructure, healthcare, education, and social welfare, leading to poor service delivery, economic instability, and eroded public trust. Despite anti-corruption laws and financial regulations, these problems persist due to systemic weaknesses in oversight, accountability, and enforcement mechanisms. This study examines the causes, impacts, and potential solutions to fund mismanagement and embezzlement, with a focus on their implications for governance and economic development. By integrating theoretical frameworks with empirical analysis, the research aims to contribute to policy reforms and academic discourse on public financial management.